Relation between criteria for evaluation of market competition - Титаренко, В. Є.; Tytarenko, V. (Видавництво Львівської політехніки, 2024)
Мета статті – розглянути, систематизувати наявні способи визначення рівня конкуренції на ринку. Сучасне ринкове середовище є на стадії послаблення глобалізації, перебудови регіональних ринків і не залишає вільного простору для комфортного існування компаній. Усі ринки та сегменти дедалі більше зазнають впливу конкуренції. Керівникам підприємств необхідно розуміти рівень концентрації ринку в кожному сегменті, щоб приймати правильні рішення залежно від його структури. Для визначення типу ринку та його структури вчені протягом останніх 100 років запропонували численні методи дослідження ринкової структури. Розглянуто найвідоміші методи визначення концентрації ринку, зокрема Індекс концентрації (CR), Індекс Герфіндаля-Гіршмана (HHI), коефіцієнт Джині, індекс Лінда та інші. А також способи оцінки ринкової влади підприємства: індекс Лернера, індекс перехресної еластичності попиту, індекс прибутковості Байна та інші. Прикладне застосування отримали методи оцінки ринкової концентрації, що базуються на ринкових частках та кількості конкурентів. Це пов’язано із доступністю даних та легкістю розрахунку. Зокрема, індекси концентрації (CR) та індекс Герфіндаля-Гіршмана (HHI) вже тривалий час застосовуються в американському та європейському антимонопольному законодавстві. Узагальнення та аналіз згаданих індексів та їх формул дали можливість визначити головні групи критеріїв для оцінки ринкової структури. Такими визначені: ринкові частки конкурентів, рівень прибутковості фірми та рівень перехресної еластичності попиту щодо замінників. Критерії оцінки ринкової структури та ринкової сили є в динамічному балансі. Перехресна еластичність попиту виступає основним регулятором рівня прибутковості підприємства на висококонцентрованих ринках. Зростання ринкової частки фірми дає більшу ринкову силу та можливість підвищення цін та прибутковості. Ріст ціни через перехресну еластичність буде підвищувати попит на товари замінники та зменшувати попит на основний товар, у такий спосіб регулюючи ціну та прибутковість. Отже, розуміння та аналіз різних індексів і критеріїв є критично важливим для ефективного управління в умовах сучасного конкурентного середовища.

The modern market environment is undergoing a phase of declining globalization, which significantly reduces the scope for companies to operate comfortably. As competition intensifies across all markets and segments, businesses face unprecedented challenges. Leaders need to understand the level of market competition in each segment to make well-informed decisions. This article explores the most well-known methods for determining market concentration and assessing the level of competition. By comparing the advantages and disadvantages of these methods, the article elucidates the interrelationships among various competition assessment criteria and their implications. Purpose. Understanding the level of competition in markets is critical for managers in their decision-making process. The numerous methods available for assessing competition can complicate this process. This article aims to summarize the existing methods for evaluating competition and identify the relationships between their evaluation criteria. Design/methodology/approach. This paper reviews and synthesizes techniques for assessing market competition that have been developed by researchers over the past several decades. The study employs a range of research methods, including analysis, synthesis, generalization, analogy, comparison, systematization, and graphical methods, to determine the relationships between different assessment criteria. This approach ensures a thorough examination of the methods and provides a robust framework for understanding their applicability. Findings. The study identifies and reviews prominent methods for assessing market competition, analyzing market structure, and calculating the market power of enterprises. These methods, proposed by scholars since the inception of this field, reveal that existing techniques can be categorized into distinct groups based on their evaluation criteria. The analysis highlights that despite the apparent simplicity of some formulas, calculating indicators related to market power remains challenging due to difficulties in obtaining accurate and objective data on profitability and, particularly, on the costs incurred by competitors. The most accessible and frequently used indicators are those derived from market structure analysis and concentration assessments. These methods are prevalent in practical applications, especially in anti-monopoly legislation, due to their effectiveness in assessing competitive dynamics and market power. Practical implications. Understanding the factors that determine market competition and shape an enterprise's market power will enable management to make quick and effective decisions regarding new products and markets. The presented correlation of various competition assessment methods and their structuring will assist in selecting the appropriate assessment method and avoid unproductive expenditure of time and resources on additional research. Originality/value. The structures and groupings of competition assessment methods provided in this paper offer a new, more comprehensive perspective on market concentration and market power. This perspective not only enhances the understanding of these concepts but also reflects their impact on enterprise profitability. The findings contribute to the ongoing development and refinement of both existing and novel methods for assessing market competition, thereby advancing the field.
Взаємозв’язок критеріїв оцінки ринкової конкуренції
Keywords: конкуренція; ринкова концентрація; ринкова влада підприємства; конкурентоспроможність; перехресна еластичність попиту; Competition; Market concentration; Market power of an enterprise; Competitiveness; Cross elasticity of demand; D40; D41; D42; D43; D49; Q21; Q31; Q41; L40; L41; 339.137.21-24